Analisis Hubungan Durasi Screen Time dengan Gejala Benign Paroxysmal Positional Vertigo (BPPV) Pada Civitas Akademika - Hadeci Lovenda Putri; Musiana Musiana; Faidana Yaumil Syifa (Universitas Pahlawan Tuanku Tambusai, 2026)
The widespread use of electronic devices, such as mobile phones and laptops, has become an integral part of the daily lives of the academic community, including faculty, educational staff, and students. This population exhibits high digital device dependency, with average usage often exceeding five hours per day. This intense and prolonged screen time is hypothesized to potentially trigger or exacerbate the symptoms of Benign Paroxysmal Positional Vertigo (BPPV), a balance disorder characterized by a sensation of spinning dizziness induced by changes in head position. This study aimed to examine the relationship between screen time duration and BPPV occurrence. A quantitative cross-sectional design was applied with a population of 315 members of the Tanjungkarang D III Nursing Department, including students, lecturers, and educational staff, and 176 respondents selected via purposive sampling. Data were collected using a demographic questionnaire and an adapted BPPV questionnaire. Most respondents (64.2%) reported 6–8 hours of daily screen time , and the median BPPV symptom score was 17.35 (range 9–27). Spearman’s correlation test showed a significant association between screen time and BPPV symptoms (r = 0.237; p = 0.002). BPPV onset is influenced by both mechanical (head position) and visual (sensory conflict) factors. Controlled screen time , regular breaks, and ergonomic practices are recommended to maintain balance.